What would Ben Graham do now? : a new value investing playbook for a global age - Towson, Jeffrey Alan, 1970- (FT Press, 2011)
As originally conceived by the legendary Benjamin Graham, traditional value investing involves purchasing relatively stable stocks and companies at a percentage below their intrinsic value. But this approach contains many hidden, U.S.-centric assumptions that simply don't work well in today's high-growth emerging markets. In this book, leading global value investor Jeffrey Towson extends and modernizes value investing, helping you apply its core principles while you access tremendous opportunities available in today's fastest-growing markets. Towson introduces the powerful Value Point system that grows out of his experience on the elite investing team selected by Prince Alwaleed, the "Arabian Warren Buffett." While retaining Graham's relentless focus on price and quality, he shows how to integrate three crucial additional forms of value into your stock assessments: the value of political access in a government-infused investment world, the value of reputation in a world of colliding markets, actors and biases, and the value of capabilities in a multi-local world. Building on these techniques, Towson presents a complete investment playbook for the next five years. Next, he shows how to invest for the next twenty years--successfully navigating the titanic market collisions that will batter investors who aren't prepared for them.